Localized input fields in rigorous coupled-wave analysis - Auer, Maximilian; Brenner, Karl-Heinz (Journal of the Optical Society of America. A, Optics, image science, and vision, 2014)
We introduce a new treatment for localized input fields in coupled-wave theory. It consists of a combination of angular spectrum decomposition and a cyclic formulation of rigorous coupled-wave analysis (RCWA), which does not require the computation of several standard RCWA calculations. The cyclic approach especially concerns the definition of the convolution matrix of the permittivity and enables the processing of multiple input plane waves in a single RCWA calculation. At the same time it ensures physically meaningful simulation results for finite truncation limits and thus inherently conserves energy. By adapting the three-dimensional (3D)-RCWA algorithm to efficiently simulate the effects of localized and arbitrarily polarized input fields to 3D volume gratings, various advanced diffraction problems such as fiber coupling, the influence of distorted plane waves, or the effects of focused beams on diffraction gratings can be investigated. Therefore, the impact of this work should concern many fields of application.
Gesehen am 29.09.2020